B blood type indicates poorer overall survival in patients with severe burn injuries: a case-control study - Wei Zhang; Xinru Wu; Yifan Liu; Yuntao Yao; Xirui Tong; Linhui Li; Dayuan Xu; Junqiang Li; Shuyuan Xian; Hanlin Sun; Jiale Yan; Guosheng Wu; et al. (Annals of Medicine)
Introduction This study focuses on the prognostic impact of ABO blood type in patients with severe burn injuries, particularly following the Kunshan explosion, exploring an under-investigated area of burn injury outcomes.Method Data from patients admitted after the Kunshan explosion were analyzed, using chi-square tests and multivariate Cox regression to investigate the relationship between ABO blood type and overall survival (OS). The study utilized various performance metrics, including the receiver operator characteristic curve (ROC), decision curve analysis (DCA) and Kaplan-Meier survival curve, for model assessment, along with a subgroup analysis for associated factors.Result The research identified ABO blood type as an independent prognostic factor in severe burn injuries. It was found that blood type O is associated with better OS, while blood type B is linked to lower OS (p = 0.001). Clinical variables such as acute kidney injury (AKI), sepsis, and other complications influenced the effect of ABO blood type on OS, according to our subgroup analysis.Conclusion Our findings indicated that blood type B was an independent and significant predictor of OS in patients with severe burn injuries, likely due to differences in immune and coagulation responses. Although the study focused on the relationship between blood type and OS, it also highlighted the importance of other factors, such as patient comorbidities and treatment approaches.